Analysis of the Effectiveness of Zakat, Infaq, and Shodaqoh in Reducing Poverty: A Case Study on Lazismu Sukoharjo in 2024/2025 - Husain, Muhammad Irsyad; Rosyadi, Imron (SAINTIS Publishing, 2025)
Poverty in Sukoharjo Regency through empowerment programs run by LAZISMU Sukoharjo. The method used is a descriptive qualitative approach with data collection techniques in the form of interviews, observation, and documentation. The results showed that the management of ZIS by LAZISMU Sukoharjo has transformed from a charitable approach to productive economic empowerment, through micro business capital programs, skills training, education scholarships, and health services. These programs have a positive impact on increasing mustahik income, reducing dependence on aid, and growing awareness of zakat in the community. However, some challenges are still faced, such as low Islamic financial literacy, limited human resources, and competition between ZIS institutions in the area. This research recommends the need for synergy between institutions and digitalization of the management system to expand the reach and effectiveness of the ZIS program. Thus, ZIS can be a strategic instrument in sustainable poverty alleviation.